The new modernist studies - Mao, Douglas (Twenty-first-century critical revisions, 2021)
"This is the first book specifically devoted to the New Modernist Studies. Bringing together a range of perspectives on the past, present, and future of this vibrant, complicated scholarly enterprise, the collection reconsiders its achievements and challenges as both a mode of inquiry and an institutional formation. In its first section, the volume offers a fresh history of the New Modernist Studies' origins amid the intellectual configurations of the end of the twentieth century and changing views of the value, influence, and scope of modernism. In the second section, a dozen leading scholars examine recent trends in modernist scholarship to suggest possible new paths of research, showing how the field continues to engage with other areas of study and how it makes a case for the ongoing meaning of modernist literature and art in the contemporary world"--
Keywords: Modernism (Literature); Modernism (Art)